A discontinuous Galerkin Finite Element Method for linear elasticity using a mixed integration scheme to circumvent shear‐locking. Issue 1 (October 2016) - Steiner, Tobias; Wriggers, Peter; Loehnert, Stefan
Abstract: Shear‐locking is a significant problem when using the Finite Element Method (FEM) with standard lower order Langrangian shape functions. To avoid this effect we introduce the discontinuous Galerkin Finite Element Method (dG‐FEM) for linear elasticity. In addition to a standard integration scheme for the dG‐FEM we develop a mixed integration scheme and compare both with established finite elements using a bending dominated benchmark. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)